O léxico como um recurso linguístico para a produção de significado: uma proposta de caracterização sistêmico-funcional - Júlia Santos Nunes Rodrigues (2022)
This thesis is part of the lexis’ studies within the systemic-functional linguistics (SFL). The main purpose of this research is to identify the principles of lexis and lexical item organization and operation in the scope of Brazilian Portuguese under a complementary perspective between lexis and grammar (HALLIDAY, MCINTOSH e STREVENS, 1964; MARTIN, 1992; HALLIDAY, 2002; FIGUEREDO, 2007; 2011). In this perspective, lexis is seen as a theoretical concept and is investigated through its own approach, adopting grammar in a complementary view, not as its origin. Problems related to modular lexis approach – lexis as filling for grammatical structures – or contiguous approach – lexis as the most delicate grammar – motivate this study, in the sense that lexis needs an explanation about how its internal processes work regarding lexis as a dimension, as well as the relations between lexical items beyond the grammatical stratum. Supported by Corpus Linguistics’ tools, a corpus of academic papers about “diabetes mellitus self-care”, written in Brazilian Portuguese and published in the last decade, a reference corpus to generate a list of items used in the development and application of the lexical probes, and a supporting corpus to contrast the results obtained under the investigations of lexical probes, the present research explores two transformation processes, through which the lexis is integrated into linguistic systems, when it is related to the paradigmatic axis in the grammatical stratum, and to the context through a process called co-extensiveness, letting lexis to be treated as one of the language dimensions. Specifically, in this research, the processes of grammar and context transformations are investigated, including mainly the development and application of lexical probes. These lexical probes could be seen as methodological resources created within this study to analyze the lexis internal processes, especially, with regard to the emergence of lexical items composed by more than one component and the formation of lexical items through the exploration of the portions that constitute them. A wider analysis of the results obtained in the present research also reveals a methodological alternative to work with lexis in a theoretical approach, which examines, through lexical probes, not only how lexical items are organized but also how they function in a language. These findings can contribute to systemic-functional theory (SFT), to translation studies regarding machine translation, and corpora-based linguistic studies.